Study of energy quantities for a hyperon in hypernuclei using a single particle potential - Lalazissis, G. A.; Grypeos, M. E.; Massen, S. E. (HNPS Advances in Nuclear Physics, 2020)
A single particle hyperon-nucleus potential is adopted for the study of various energy quantities of a hyperon (Y) in hypernuclei.Approximate semi-empirical formulae for the ground state (g.s.) binding energy and for the oscillator spacing hωΛ of a Λ in hypernuclei are proposed. The region of their validity is discussed.The g.s. binding energies of the Ξ- hyperon in the few known Ξ- hypernuclei are also analyzed and a comparison of the volume integrals of the Ξ- nucleon and Λ nucleon potentials |V_{ΞN}I and |V_{ΛΝ)| is made. The value of the ratio γ=V_{ΞΝ}/|V_{ΛN}| is found to be ~0.8. Such a conclusion is also obtained by using in the same way other potential models such as the Woods-Saxon one.